Enough! : how to liberate yourself and remake the world with just one word - McCammon, Laurie (Conari Press, 2016)
"We Are Enough, We Have EnoughDo you, like so many of us, believe that you will never have enough time, money, talent, or love to be truly happy? Do you think you're not good enough, not rich enough or thin enough or smart enough, to have the life you want? Or that the problems in your community and the world around you could be solved if only there were more to go around? Everywhere, all the time, we get this message that there is something lacking, something more, something better to strive for. In fact, the idea that there isn't enough or you aren't enough is so deeply ingrained in us and into our culture that it holds sway over pretty much every aspect of our lives, from how we perceive our self-worth and our skills as parents, friends, and partners (I am not enough) to the ways in which we are taught and governed. But what if it's a lie? Author and activist Laurie McCammon wrote this book to show you that it is all a lie. Discover how your own never-enough thinking has been limiting you and how to challenge it in all the places it lurks. Let Laurie show you how to develop a sense of enoughness that can change not only how you feel about yourself but how you view time, your relationships, your work, and the possibilities for helping to shape a better world"--